MODEL PENGAWASAN OTORITAS JASA KEUANGAN TERHADAP BISNIS FINTECH DI INDONESIA - ARI RAHMAD HAKIM BF; I GUSTI AGUNG WISUDAWAN; YUDHI SETIAWAN (GANEC SWARA, 2022)
This study is aimed at reviewing and analyzing the Financial Services Authority's supervisory model for fintech businesses in Indonesia. The type of research used in this research is Normative Research with a Statute Approach and a Conceptual Approach. This study also uses legal materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials used in this research is Documentation Study with Analysis of Legal Materials, namely Qualitative Descriptive Analysis. The supervisory model that should be carried out by OJK is a combination or mixed supervision model, namely by combining direct or active supervision with indirect or passive supervision. Law enforcement in dealing with problematic Fintech cases is the application of legal sanctions both administratively, criminally and civilly